The facultative intracellular symbiont Lariskella is neutral for lifetime fitness and spreads through cytoplasmic incompatibility in the leaffooted bug, Leptoglossus zonatus - Umanzor, Edwin F.; Kelly, Suzanne E.; Ravenscraft, Alison; Matsuura, Yu; Hunter, Martha S. (Frontiers in Microbiology, 2025)
The maternally-inherited, intracellular bacterium Lariskella (Alphaproteobacteria: Midichloreaceae) has been widely detected in arthropods including true bugs, beetles, a wasp, a moth, and pathogen-vectoring fleas and ticks. Despite its prevalence, its role in the biology of its hosts has been unknown. We set out to determine the role of this symbiont in the leaffooted bug, Leptoglossus zonatus (Hempitera: Coreidae). To examine the effects of Lariskella on bug performance and reproduction as well as in possible interactions with the bug’s obligate nutritional symbiont, Caballeronia, bugs were reared in a factorial experiment with both Lariskella and Caballeronia positive and negative treatments. Lifetime survival analysis (~120 days) showed significant developmental delays and decrease in survival for bugs that lacked Caballeronia, and Caballeronia-free bugs did not reproduce. However, among the Caballeronia carrying treatments, there were no significant differences in lifetime survival or reproduction in treatments with and without Lariskella, suggesting this symbiont is neutral for overall bug fitness. To test for reproductive manipulation, crossing among Lariskella-positive and negative individuals was performed. When Lariskella-negative females were mated with Lariskella positive males, fewer eggs survived early embryogenesis, consistent with a cytoplasmic incompatibility (CI) phenotype. Wild L. zonatus from California and Arizona showed high but not fixed Lariskella infection rates. Within individuals, Lariskella titer was low during early development (1st–3rd instar), followed by an increase that coincided with development of reproductive tissues. Our results reveal Lariskella to be among a growing number of microbial symbionts that cause CI, a phenotype that increases the relative fitness of females harboring the symbiont. Understanding the mechanism of how Lariskella manipulates reproduction can provide insights into the evolution of reproductive manipulators and may eventually provide tools for management of hosts of Lariskella, including pathogen-vectoring ticks and fleas.